Understanding organic aerosols in Bogotá, Colombia: In-situ observations and regional-scale modeling. (1st September 2022) - Ballesteros-González, Karen; Espitia-Cano, Sebastian Orlando; Rincón-Caro, Maria Alejandra; Rincón-Riveros, Juan Manuel; Perez-Peña, Maria Paula; Sullivan, Amy; Morales Betancourt, Ricardo
Abstract: Organic aerosol (OA) is one of the major components of fine atmospheric aerosol particles. Recent field campaigns and modeling studies in Colombia have demonstrated the presence of a large OA fraction in urban and rural aerosols. In this work we focus on constraining the sources associated with OA and its precursors over the city of Bogotá, Colombia. We used PM2.5 chemical speciation data from field campaigns carried out during 2018 to evaluate the ability of a regional transport model to reproduce and explain the observed OA. The samples were collected at three sites during high- and low-aerosol concentration seasons in the region. We used The Weather Research and Forecasting Model coupled with Chemistry (WRF-Chem) with two different chemical mechanisms and aerosol schemes, RACM/MADE-VBS and MOZART/MOSAIC, in conjunction with the detailed in-situ aerosol chemical speciation observations to analyze the seasonality of OA in the city of Bogotá, and to establish the most relevant sources. Simulations were carried out for the same periods for which data is available, spanning a high biomass burning (BB) season (February 2018) and a low biomass burning season (September 2018). We demonstrated that long-range transport of BB emissions from Northern Amazonia can episodically increase aerosol loading during September, while BB activity in the Grasslands of the Orinoco River Basin are the main source during February. The two aerosol schemes utilized in this work reproduce the observed seasonal variations in total fine aerosol concentration, with a difference between February and September of 10 μ g m −3 . The comparison between aerosol schemes demonstrated that MOZART/MOSAIC consistently predicted more OA with a larger SOA:OA ratio than in the RACM/MADE-VBS experiment. SOA dominates the OA fraction by 66% for RACM/MADE-VBS and 74% for MOZART/MOSAIC during February and 69% for RACM/MADE-VBS and 71% for MOZART/MOSAIC during September. These differences between organic aerosol burden between the mechanisms used in this study may be attributed to the different treatment of SOA gas/particle partitioning in the schemes. Highlights: WRF-Chem simulations and in-situ PM2.5 chemical composition data were used to understand the contribution of OA over Bogotá. Biomass burning plumes from Northern Amazonia and from the Orinoco River Grassland can severely impact the region. Field data shows that OA contributes over 40% to PM2.5 in the city. The model underpredicts organic aerosols, with the MOZART/MOSAIC scheme predicting higher POA and SOA than RACM/MADE-VBS.